2009
DOI: 10.1002/jrs.2172
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent Raman scattering studies of polycrystalline BiFeO3 bulk ceramics

Abstract: This work reports the temperature-dependent Raman scattering study of mutiferroic BiFeO 3 (BFO) bulk ceramics in a wide temperature range of 93-843 K. The polycrystalline samples are sintered at four different temperatures and characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), vibrating sample magnetometry, differential scanning calorimetry (DSC), and optical microscopy. The microstructure shows remarkable changes in terms of grain size and domain pattern as the sintering tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
67
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 32 publications
13
67
0
Order By: Relevance
“…From Figure 4(a), we can observe the following features in Raman spectra with increase of temperature: (i) reduction in the peak intensity, (ii) lower frequency values (see dotted line in Figure 4(a)), (iii) marked widening of the peaks, and (iv) pronounced decrease in the intensity of Raman modes (this effect is more pronounced in high wavenumber peaks (>400 cm À1 ), which disappears near T N $ 620 K). Similar observations were reported by other researchers in bulk and single-crystal BFO, 25,48,50 and they attributed this effect to thermal broadening and thermal disorder.…”
Section: Raman Spectroscopysupporting
confidence: 91%
See 2 more Smart Citations
“…From Figure 4(a), we can observe the following features in Raman spectra with increase of temperature: (i) reduction in the peak intensity, (ii) lower frequency values (see dotted line in Figure 4(a)), (iii) marked widening of the peaks, and (iv) pronounced decrease in the intensity of Raman modes (this effect is more pronounced in high wavenumber peaks (>400 cm À1 ), which disappears near T N $ 620 K). Similar observations were reported by other researchers in bulk and single-crystal BFO, 25,48,50 and they attributed this effect to thermal broadening and thermal disorder.…”
Section: Raman Spectroscopysupporting
confidence: 91%
“…Table III. From this table, we can observe that a similar number of modes were reported for BFO at 93 K and at RT by Kothari et al 46 and Rout et al 25 It was noted that the Raman spectra of BNFM at low temperature (83 K) and RT (Figure 4(a) and Table III) are very similar, supporting the idea that the rhombohedral (R3c space group) structure is retained in Nd, Mn co-doped BFO ceramics; similar results were obtained by Haumont et al 48 for BFO single-crystals. Singh et al 49 have reported A 1 and low frequency E modes corresponding to Bi-O bonds, whereas higher frequency E modes are related to Fe-O bonds.…”
Section: Raman Spectroscopysupporting
confidence: 81%
See 1 more Smart Citation
“…Similar observations have been reported for some other perovskite compounds. [22][23][24][25] Features of the B 2g ͑7͒, A g ͑4͒, and A g ͑3͒ modes are associated with the vibration of oxygen ions. Their frequencies decrease with increasing La content, because of the increase in the RE-O and Cr-O force constants.…”
Section: B Raman Spectramentioning
confidence: 99%
“…Probing IR-active low-energy excitations is hindered by a lack of sufficiently large single crystals. Raman-active phonons of the rhombohedral R3c BiFeO 3 structure have been reported for single crystals, [6][7][8] polycrystalline ceramics, [9][10][11] and thin films, 12,13 however, there is a significant discrepancy between the claimed phonon frequencies and symmetry representations. A possible explanation for such inconsistences between the various experimental results is the presence of oblique phonon modes, which show a continuous variation of frequency along the phonon propagation vector with respect to the crystallographic axis of the probed specimen.…”
Section: Introductionmentioning
confidence: 99%